THE EFFECT OF USING COLLABORATIVE WRITING METHOD ON STUDENTS’ WRITING RECOUNT TEXT AT GRADE TEN OF SMK YP 1 HKBP PEMATANGSIANTAR - Herman Herman; Theresia Aprina Rajagukguk; Partohap Saut Raja Sihombing (Acitya: Journal of Teaching and Education, 2020)
This study was focused on the effect of using collaborative writing on students’ achievement in writing recount text. The objective of this research was to find out the significant effect of collaborative writing on students’ achievement in writing recount text at students grade ten in SMK YP 1 HKBP Pematangsiantar. Two classes was taken as the sample of this research. The class X-MP as the experimental group that taught by using collaborative writing and X-MM as the control class taught by conventional method. This research design is quantitative research were gained by assessing the students’ writing skills through the pretest and posttest. The instrument of collecting data was writing test. After collecting data, it was found the main score of pretest to post test in experimental group was 48.47 to 89,647. The data were analyzed by using t-test formula. The result showed that the t-test is higher than the value of t-table. (5. 68 > 1.69 (α = 0.05)) with the degree of freedom (df) = 32. Based on the data analysis of the study, the result indicates that the alternative hypothesis (Ha) was accepted. It means that there is a significant effect of using Collaborative writing on students’ achievement in writing recount text of students grade ten in SMK YP1 HKBP Pematangsiantar.